NURSING CARE OF PATIENT WITH SEPSIS DUE TO BLAST INJURY - Efris Kartika Sari; Nisofa Nisofa; Rendi Yoga Saputra; Masriami Masriami; Muhammad Khoirudin; Richardus MGP Lahamukang; Klara Yunita Inuq Thomas (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
Blast injury is an injury due to the mechanism of barotrauma (involving excessive pressure) which results in organ trauma. Trauma and extensive injury can progress to sepsis condition to the patient. A man is hospitalized due to blast injury. The patient suffered a third-degree burn involving 18% total body surface area locateÂ in the abdomen and right thigh, and right femoral trauma. The patient has right hip disarticulation and abdominal wound debridement surgery. After surgery, the patient has decreased consciousness and respiratory failure so that he was treated in the intensive care unit. The nursing assessment identified that patient has sepsis conditions. Nursing problems of the patient are ineffective airway clearance, impaired spontaneous ventilation, the risk for shock, and impaired tissue integrity. The nurse performs nursing care to maintain airway patency, provide adequate ventilation, maintain hemodynamic stability, and optimize the wound healing process of the patient.